AutoParBench: A Unified Test Framework for OpenMP-based Parallelizers - Mendonça, Gleison Souza Diniz; Pereira, Fernando Magno Quintão; Liao, Chunhua (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2021: Anais do XXXIV Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2021.15755, 2021)
After decades of advances in techniques of automatic parallelization, software developers can count, today, on many different tools that transform a program, so that it runs in parallel. Yet, most of these tools are still considered research artifacts. They contain latent bugs, often consequence of a sparsity of testing frameworks for autoparallelizers. This dissertation describes one such framework: AutoParBench - the product of a cooperation between UFMG's Compilers Lab, and Lawrence Livermore National Laboratory. AutoParBench is today publicly available, and has been successfully used to find three zero-day bugs in the Intel C Compiler. Its usage also uncovered problems in more research-oriented tools: 2 bugs in DawnCC, 4 in Rose AutoPar and 2 in Cetus. All these bugs have been confirmed, and some of them have been already fixed as an aftermath of this work.